Persistence of third aortic arch with fourth aortic arch agenesis. Issue 6 (June 1986) - Ekteish, F M; Hajar, R; Folger, G M
Abstract : This report describes a case in which a persistent third aortic arch connection partly palliated interruption of the aortic arch. The malformation occurred without other cardiovascular abnormality in a newborn infant in whom the principal diagnostic clinical finding was the absence of all peripheral pulses except for those of the right brachial and carotid arteries. Echocardiographic and angiocardiographic examination showed a continuation of the left internal carotid artery to the descending aorta by way of an arching communication.